2015
DOI: 10.1021/jacs.5b03573
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Macrocycle Threading by a Fluorescent Dye–Polymer Conjugate in Water with Nanomolar Affinity

Abstract: A macrocyclic tetralactam host is threaded by a highly fluorescent squaraine dye that is flanked by two polyethyleneglycol (PEG) chains with nanomolar dissociation constants in water. Furthermore, the rates of bimolecular association are very fast with kon ~106–107 M−1s−1. The association is effective under cell culture conditions and produces large changes in dye optical properties including turn-on near-infrared fluorescence that can be imaged using cell microscopy. Association constants in water are ~1000 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(78 citation statements)
references
References 41 publications
1
75
0
2
Order By: Relevance
“…Previously, we reported the structure and properties of threaded, single-station complex 6C ⊃S . 33 As a fluorescent probe in cell culture, it exhibited no specific cell affinity and was observed to slowly enter living cells over several hours. Thus, in this present mouse imaging study, the threaded complex 6C ⊃S and new two-station version 2(6C) ⊃S3S were expected to act as non-targeted control probes that cleared from the blood stream through the kidneys with little retention in other organs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported the structure and properties of threaded, single-station complex 6C ⊃S . 33 As a fluorescent probe in cell culture, it exhibited no specific cell affinity and was observed to slowly enter living cells over several hours. Thus, in this present mouse imaging study, the threaded complex 6C ⊃S and new two-station version 2(6C) ⊃S3S were expected to act as non-targeted control probes that cleared from the blood stream through the kidneys with little retention in other organs.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that mixing S and 6C in water at 20 °C formed the single-station untargeted complex 6C ⊃S with an association constant ( K a ) of 1 × 10 9 M −1 and threading rate k on of 130 M −1 s −1 33 . Essentially the same values of K a and k on were observed when S and 6B were mixed in water to form the single-station targeted complex 6B ⊃S .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic profiles were fitted to the standard second order kinetic equation using Origin Lab ™ 8.6 software. 15 …”
Section: Methodsmentioning
confidence: 99%
“…46 The empty macrocycle has a highly preorganized structure and the binding cavity is lined with a synergistic mixture of convergent polar hydrogen bonding sites and hydrophobic surfaces. Most biological association systems, including biotin/(strep)avidin, use similar types of amphiphilic binding pockets to recognize complementary guests with high affinity and shape selectivity.…”
Section: Host•guest Mimics Of Biotin/(strept)avidinmentioning
confidence: 99%